A G-quadruplex-based colorimetric assay of S1 nuclease activity and inhibition. Issue 13 (15th June 2015) - Shi, Bingfang; Qin, Yingfeng; Huang, Mengjiao; Zhao, Jingjin; Su, Yubin; Zhao, Shulin
Abstract : A label-free colorimetric assay based on the catalysis of G-quadruplex/hemin DNAzyme was developed for highly sensitive and specific detection of S1 nuclease activity and inhibition. Abstract : A label-free colorimetric assay based on the catalysis of G-quadruplex/hemin DNAzyme was developed for highly sensitive and specific detection of S1 nuclease activity and inhibition. In this system, G-rich DNA is used as the substrate for G-quadruplexes. G-rich DNA binds hemin to form G-quadruplex/hemin DNAzyme with peroxidase-like activity, which catalyzes the oxidation of 2, 2′-azino-bis(3-ethylbenzothiazoline)-6-sulfonate disodium salt (ABTS) by H2 O2 to generate colored ABTS˙ + . In the presence of S1 nuclease, G-rich DNA was cleaved into small fragments, resulting in the formation of a lower amount of G-quadruplexes and low absorbance. The difference of absorbance before or after enzymatic digestion can be used to monitor the S1 nuclease activity and inhibition. This sensing platform can detect the S1 nuclease activity in a linear range of 0.03–5 U mL −1 with a detection limit of 0.014 U mL −1 . The present strategy also enables "naked-eye" detection of the S1 nuclease activity with an actual detection limit of 0.03 U mL −1, which makes it more convenient than other methods that rely on instrumentation. More importantly, adenosine triphosphate (ATP) is found to well inhibit the activity of S1 nuclease when using certain G-quadruplex DNA as a substrate, which provides a promising application in drug screening based on the inhibition of S1 nuclease.